Dietary supplementation with lactose or artificial sweetener enhances swine gut Lactobacillus population abundance. Issue 1 (2nd January 2014) - Daly, Kristian; Darby, Alistair C.; Hall, Neil; Nau, Alexandra; Bravo, David; Shirazi-Beechey, Soraya P.
<x content-type="archive" xml:space="preserve">Abstract</x> The commensal bacteria Lactobacillus are widely used as probiotic organisms conferring a heath benefit on the host. They have been implicated in promoting gut health via the stimulation of host immunity and anti-inflammatory responses, as well as protecting the intestinalmucosa against pathogen invasion. Lactobacilli grow by fermenting sugars and starches and produce lactic acid as their primary metabolic product. For efficient utilisation of varied carbohydrates, lactobacilli have evolved diverse sugar transport and metabolic systems, which are specifically induced by their own substrates. Many bacteria are also capable of sensing and responding to changes in their environment. These sensory responses are often independent of transport or metabolism and are mediated through membrane-spanning receptor proteins. We employed DNA-based pyrosequencing technology to investigate the changes in the intestinal microbiota of piglets weaned to a diet supplemented with either a natural sugar, lactose or an artificial sweetener (SUCRAM®, consisting of saccharin and neohesperidin dihydrochalcone (NHDC); Pancosma SA). The addition of either lactose or saccharin/NHDC to the piglets' feed dramatically increased the caecal population abundance of Lactobacillus, with concomitant increases in intraluminal lactic acid concentrations. This is the first report of the prebiotic-like effects of saccharin/NHDC, an artificial sweetener, being able to influence the commensal gut microbiota. The identification of the underlying mechanism(s) will assist in designing nutritional strategies for enhancing gut immunity and maintaining gut health.